Greening the desert : agro-economic impact of Indira Gandhi canal of Rajasthan - Koshteh M. H., Karim (Delhi : Renaissance, 1995)
Agro-economic impact of Indira Gandhi Nahar Project on agricultural development of Rajasthan, India.
Originally presented as the author's thesis (Ph. D.--Banaras Hindu University).
Keywords: Indira Gandhi Nahar Project; Desert ecology -- India -- Rajasthan; Agriculture -- Economic aspects -- India -- Rajasthan; Green Revolution -- Environmental aspects -- India -- Rajasthan